Taiwan Austronesian Language Heritage Connecting Pacific Island Peoples: Diplomacy And Values - Blundell, David (Penerbit Universiti Sains Malaysia (USM Press), 2011)
As we engage in the current Pacific arena of diplomacy and cultural values, the position of Taiwan as an early linguistic factor in the dispersal of its languages is important to observe. The region is increasingly using this linguistic heritage to seek collaboration and partnership. Since Neolithic prehistory, Taiwan has ushered in the Austronesian languages that became about 1,200 in number spreading across most of Island Southeast Asia and Oceania for several thousand years, extending from origins, with examples found in the Formosan languages, through the Malayo-Polynesian languages of the islands of Philippines, Malaysia, Indonesia, Micronesia, Melanesian islands, Polynesia, and across the Indian Ocean in Madagascar. These languages are valuable, regardless of their extent, influence, or number of speakers, as part of the basic richness of humanity—a farreaching interconnecting legacy of communication and worldviews. This article explores the concept of Taiwan and Austronesia—positioning historical roots and contemporary languages and cultures as valuable peaceful and sustainable development tools for island inter-connectivity across the Pacific that can be used to seek collaboration and partnership due to their association with heritage.